Centralized registry for COVID-19 research recruitment: Design, development, implementation, and preliminary results. Issue 1 (14th July 2021) - Peeler, Anna; Miller, Hailey; Ogungbe, Oluwabunmi; Lewis Land, Cassia; Martinez, Liz; Guerrero Vazquez, Monica; Carey, Scott; Murli, Sumati; Singleton, Megan; Lacanienta, Cyd; Gleason, Kelly; Ford, Daniel; et al.
Abstract: Background: The Coronavirus Disease 2019 (COVID-19) pandemic has had substantial global morbidity and mortality. Clinical research related to prevention, diagnosis, and treatment of COVID-19 is a top priority. Effective and efficient recruitment is challenging even without added constraints of a global pandemic. Recruitment registries offer a potential solution to slow or difficult recruitment. Objectives: The purpose of this paper is to describe the design and implementation of a digital research recruitment registry to optimize awareness and participant enrollment for COVID-19-related research in Baltimore and to report preliminary results. Methods: Planning began in March 2020, and the registry launched in July 2020. The primary recruitment mechanisms include electronic medical record data, postcards distributed at testing sites, and digital advertising campaigns. Following consent in a Research Electronic Data Capture survey, participants answer questions related to COVID-19 exposure, testing, and willingness to participate in research. Branching logic presents participants with studies they might be eligible for. Results: As of March 24, 2021, 9010 participants have enrolled, and 64.2% are female, 80.6% are White, 9.4% are Black or African American, and 6% are Hispanic or Latino. Phone outreach has had the highest response rate (13.1%), followed by email (11.9%), text (11.4%), and patient portal message (9.4%). Eleven study teams have utilized the registry, and 4596 matches have been made between study teams and interested volunteers. Conclusion: Effective and efficient recruitment strategies are more important now than ever due to the time-limited nature of COVID-19 research. Pilot efforts have been successful in connecting interested participants with recruiting study teams.